Tratamento do quelóide de lóbulo da orelha com infiltração de triancinolona(10 mg/ml, 20 mg/ml ou 40 mg/ml), retirada cirúrgica e compressão da cicatriz - Silvia Mandello Carvalhaes (2008)
The treatment of keloid is still controversial with no procedure clearly more effective than the others. With the purpose to establish the best treatment for ear lobe keloids, 46 consecutive patients with 81 ear lobe keloids were prospectively studied. The treatment protocol was as follows: 1- monthly intralesional injection of triamcinolone (TCN) forthree months; 2- keloid resection at the fourth month along with intraoperative TCN injection; 3- local application of an ear ring pressure device for two months; 4- monthly injection of TCN for another two months after surgery. Patients were divided into three groups: Group 1 (20 patients with 33 keloids) received 40mg/ml(2mg/ mm³ of lesion)TCN; Group 2 received 20mg/ml (1mg/ mm³ of lesion)TCN (16 patients with 28 keloids); and Group 3 (0,5mg/ mm³ of lesion)TCN (10 patients with 10 keloids) received TCN at 10mg/ml. Both primary and recurrent keloids were included in this series. TCN injection before surgery was aimed at shrinkage and softening of the lesion as well as to symptomrelief. Dose application varied according to the lesion volume that was carefully measured with a digital milimeter gauge. Higher doses were used for large lesions. After surgery, an ear ring-like device was used with the purpose to keep the scar under a closing pressure above 24 mmHg for 4 months. The follow-up period was 24 months. Preoperativetreatment response to TCN was defined as symptom improvement and lesion shrinkage and or softening. Group 3 was interrupted early in the study due to evident treatment failure when compared to Groups 1 and 2. Complications consisted of anaphylaxis in three patients, two in group 1 and one in Group 2, and one patient presented with wound infection in Group 2. Statistical analysis showed no difference in the results for Groups 2 and 3. Therefore, in this study the best treatment for ear lobe keloids was the use of intralesional injection of TCN 20 mg/ml for three months, followed by surgery and intraoperative TCN, local pressure device application for 4 months, and further monthly steroid injection at the surgical site for another 2 months.